PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN POESPA SALON & SPA BEKASI BARAT - Hotman Napitupulu (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
Service quality in this study has a positive and significant effect on customer satisfaction, so the first hypothesis put forward "allegedly a positive and significant influence on service quality on customer satisfaction" can be accepted.